Pengaruh Brand Awareness Terhadap Repurchase Intention yang Dimediasi oleh Brand Loyalty dan Brand Equity - Vania Taradiva Aristawati; Rini Kuswati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of brand awareness on repurchase intention for Lemonilo products, with brand loyalty and brand equity as mediating variables. This research is conducted due to inconsistencies in previous studies regarding the relationship between brand awareness and repurchase intention. A quantitative method with the Partial Least Square-Structural Equation Modeling (PLS-SEM) approach was used, analyzed with SmartPLS 3 software. Data were collected through an online survey using Google Forms and purposive sampling, involving 202 university students in Indonesia who had purchased Lemonilo instant noodles. The results indicate that brand loyalty and brand equity significantly influence repurchase intention. However, brand awareness does not directly affect repurchase intention but contributes indirectly through increased brand loyalty and brand equity. These findings suggest that brand recognition alone is insufficient to drive repurchase intention without strong loyalty and perceived brand value.